2015
DOI: 10.3389/fimmu.2015.00498
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Promotes Intracellular Growth of Mycobacterium by Inhibiting Apoptosis of Infected Macrophages

Abstract: The fate of infected macrophages is a critical aspect of immunity to mycobacteria. By depriving the pathogen of its intracellular niche, apoptotic death of the infected macrophage has been shown to be an important mechanism to control bacterial growth. Here, we show that IL-17 inhibits apoptosis of Mycobacterium bovis BCG- or Mycobacterium tuberculosis-infected macrophages thus hampering their ability to control bacterial growth. Mechanistically, we show that IL-17 inhibits p53, and impacts on the intrinsic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
5
23
1
Order By: Relevance
“…Lombard also highlights that the IL-17A-driven exacerbation of inflammation observed in several circumstances may lead to tissue destruction. IL-17A is overproduced in response to high mycobacterial loads in the mouse [35] or in humans infected with multidrug-resistant Mtb strains resulting in high antigen loads [36], leading to an unfavorable clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Lombard also highlights that the IL-17A-driven exacerbation of inflammation observed in several circumstances may lead to tissue destruction. IL-17A is overproduced in response to high mycobacterial loads in the mouse [35] or in humans infected with multidrug-resistant Mtb strains resulting in high antigen loads [36], leading to an unfavorable clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in anti-IL-17A-antibody-treated mice gene expression patterns associated with macrophage polarization and pro- and anti-apoptotic responses were not affected. In fact, a recent study showed that IL-17A actually promotes intracellular growth of M. tuberculosis by inhibiting apoptosis of infected macrophages68. Thus, while anti-TNFα antibody treatment prevents apoptosis of mycobacterially infected macrophages enabling bacterial growth, anti-IL-17A treatment may actually limit intracellular growth of M. tuberculosis by enhancing apoptosis of infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Further mechanistic investigations into the host–pathogen interactions during transition from dormant to reactivated pathogen states utilizing the in vitro human M. tuberculosis microgranuloma model are ongoing to address the obvious limitations of this observational study. Whereas anti‐TNFα antibody treatment may prevent apoptosis of M. tuberculosis ‐infected macrophages enabling bacterial growth, 13 a recent study showed that IL‐17A actually promotes intracellular growth of M. tuberculosis by inhibiting apoptosis of infected macrophages 60 . Hence, anti‐IL‐17A treatment may limit intracellular growth of M. tuberculosis by enhancing apoptosis of infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas anti-TNFα antibody treatment may prevent apoptosis of M. tuberculosis-infected macrophages enabling bacterial growth, 13 a recent study showed that IL-17A actually promotes intracellular growth of M. tuberculosis by inhibiting apoptosis of infected macrophages. 60 Hence, anti-IL-17A treatment may limit intracellular growth of M. tuberculosis by enhancing apoptosis of infected macrophages.…”
Section: Discussionmentioning
confidence: 99%